S6N2O15—A Nitrogen‐Poor Sulfur Nitride Oxide, and the Anhydride of Nitrido‐tris‐Sulfuric Acid. Issue 39 (4th August 2020) - van Gerven, David; Wickleder, Mathias S.
Abstract: The reaction of hexachlorophosphazene, P3 N3 Cl6, with SO3 leads to the new sulfur nitride oxide S6 N2 O15 . The compound displays an extraordinarily low nitrogen content and exhibits a bicyclic cage structure according to the formulation N{S(O)2 O(O)2 S}3 N, with both nitrogen atoms in trigonal planar coordination of sulfur atoms. Interestingly, the new nitride oxide can be also seen as the anhydride of nitrido‐ tris ‐sulfuric acid, N(SO3 H)3 . Abstract : The cage type molecule S6 N2 O15 is not only a new sulfur nitride oxide, but also the anhydride of the rarely seen nitrido‐ tris ‐sulfuric acid. Interestingly, the unique compound is obtained in high yields from reactions of SO3 with P3 N3 Cl6 .